Casimir effect for perfect electromagnetic conductors (PEMCs): a sum rule for attractive/repulsive forces. (16th April 2018) - Rode, Stefan; Bennett, Robert; Buhmann, Stefan Yoshi
Abstract: We discuss the Casimir effect for boundary conditions involving perfect electromagnetic conductors, which interpolate between perfect electric conductors and perfect magnetic conductors. Based on the corresponding reciprocal Green's tensor we construct the Green's tensor for two perfectly reflecting plates with magnetoelectric coupling (non-reciprocal media) within the framework of macroscopic quantum electrodynamics. We calculate the Casimir force between two arbitrary perfect electromagnetic conductor plates, resulting in a universal analytic expression that connects the attractive Casimir force with the repulsive Boyer force. We relate the results to a duality symmetry of electromagnetism.